2016
DOI: 10.18632/oncotarget.14064
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of circulating tumor DNA in gastric cancer: a meta-analysis

Abstract: BackgroundCirculating tumor DNA (ctDNA) has offered a minimally invasive approach for detection and measurement of gastric cancer (GC). However, its diagnostic and prognostic value in gastric cancer still remains unclear.ResultsA total of 16 studies comprising 1193 GC patients met our inclusion criteria. The pooled sensitivity and specificity were 0.62 (95% confidence intervals (CI) 0.59−0.65) and 0.95 (95% CI 0.93–0.96), respectively. The AUSROC (area under SROC) curve was 0.94 (95% CI 0.89–0.98). The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 40 publications
1
59
0
Order By: Relevance
“…a positive correlation between ctDNA detection and the total number of tumor cells in the primary tumor in the early stage of pancreatic cancer. Gao and colleagues (19) showed that the presence of ctDNA was associated with larger tumor size, TNM stage, and Helicobacter pylori infection in gastric cancer. Similarly, we demonstrated that the positive rate of ctDNA detection was positively correlated with tumor size and Ki-67 in advanced GIST patients.…”
Section: Discussionmentioning
confidence: 99%
“…a positive correlation between ctDNA detection and the total number of tumor cells in the primary tumor in the early stage of pancreatic cancer. Gao and colleagues (19) showed that the presence of ctDNA was associated with larger tumor size, TNM stage, and Helicobacter pylori infection in gastric cancer. Similarly, we demonstrated that the positive rate of ctDNA detection was positively correlated with tumor size and Ki-67 in advanced GIST patients.…”
Section: Discussionmentioning
confidence: 99%
“…CTCs and ctDNA may be of prognostic value in several gastrointestinal cancers, where the biggest impact may be their detection before therapeutic intervention. As a cancer (or minimal residual disease) evolves with time and treatment, selection pressure from surgery, chemotherapy or radiotherapy, or tumoricidal immunity could stimulate the expansion of tumour subclones ( Fig .…”
Section: Clinical Relevance In Gastrointestinal Cancersmentioning
confidence: 99%
“…They further demonstrated that ctDNA detection after therapy predicted shorter recurrence‐free survival both in patients who did not receive chemotherapy and in those who did. A meta‐analysis of mixed‐stage gastric cancer demonstrated significantly shorter disease‐free and overall survival in patients in whom ctDNA was detected. This prognostic value has been confirmed for localized gastric cancer in at least one separate study.…”
Section: Clinical Relevance In Gastrointestinal Cancersmentioning
confidence: 99%
“…In pathological analysis, traditional surgical specimens are used as the gold standard for obtaining fundamental information for clinical decision-making. However, obtaining such specimen directly from tumors is an invasive procedure and can delay the observation of tumor dynamic changes after treatment [39]. Cancers are known to shed tumor cell DNA into the blood stream [34], and examining the levels and mutations in ctDNA can provide almost realtime information regarding tumor status.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous meta-analyses have reported that the diagnostic accuracy of quantitative analysis of ctDNA is superior to conventional biomarkers for the diagnosis of several cancers, including ovarian cancer [22], lung cancer [45], gastric cancer [39], and colon cancer [46].…”
Section: Discussionmentioning
confidence: 99%